2004
DOI: 10.1002/ajh.20089
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic markers and the sepsis‐related organ failure assessment score in patients with disseminated intravascular coagulation in an intensive care unit

Abstract: We investigated the correlation between disseminated intravascular coagulation (DIC) score and hemostatic parameters and sepsis-related organ failure assessment (SOFA) score with clinical outcome of patients with DIC in an intensive care unit (ICU). The SOFA score was markedly elevated in patients with DIC relative to patients without DIC and significantly higher in non-survivors than in survivors. Abnormalities in almost all hemostatic parameters were significant in patients with DIC, but there was no signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 31 publications
5
47
0
2
Order By: Relevance
“…In our study, a significant difference was found in DIC score between overt and non-overt DIC; in addition, a significant correlation was found between DIC score and SOFA score only in overt DIC, suggesting that the severity of DIC may be an important determinant of outcome. 47 In accordance with our results, Toh and Downey 22 demonstrated that a score of 5 or more could diagnostically define patients with a poor prognosis from hemostatic dysfunction, independent of developing overt DIC. 20 Different study designs by Toh and Downey in different patient populations found that a worsening coagulopathy augers a worse outcome in patients with severe sepsis and increased development of new organ failure.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, a significant difference was found in DIC score between overt and non-overt DIC; in addition, a significant correlation was found between DIC score and SOFA score only in overt DIC, suggesting that the severity of DIC may be an important determinant of outcome. 47 In accordance with our results, Toh and Downey 22 demonstrated that a score of 5 or more could diagnostically define patients with a poor prognosis from hemostatic dysfunction, independent of developing overt DIC. 20 Different study designs by Toh and Downey in different patient populations found that a worsening coagulopathy augers a worse outcome in patients with severe sepsis and increased development of new organ failure.…”
Section: Discussionsupporting
confidence: 92%
“…Since DIC is still a fatal condition [20], it is important to diagnose it early through the use of hemostatic molecular markers [21]. The International Society of Thrombosis and Haemostasis (ISTH) established diagnostic criteria for overt-DIC using fibrinrelated markers such as D-dimer [22].…”
Section: Introductionmentioning
confidence: 99%
“…During DIC, circulating thrombin–antithrombin (TAT)complexes are considered a measure of coagulation, and tissue plasminogen activator (tPA), its inhibitor plasminogen activator inhibitor (PAI) and plasmin–α 1 -antiplasmin (PAP) complexes are considered measures of fibrinolysis 8–21. Indeed, inhibition of fibrinolysis activation by PAI is an important predictor of multiple organ dysfunction and has a relatively high predictive value for a poor outcome in sepsis and DIC 8 9 13 14 16 19–21 27 28. However, it is unclear whether PAI is an independent predictor of mortality or a surrogate for multiple organ dysfunction in patients with septic DIC 21.…”
Section: Introductionmentioning
confidence: 99%